The Influence of Job Stress, Job Boredom, and Technology Accessibility on Cyber-Loafing Behavior in Online Customer Service Employees - Sidjabat, Sonya; Purwati, Sri; Nugroho, Judianto Tjahjo; Nawangwulan, Irma M; Karyadi, Haris; Lubis, Fatimah Malini (Journal of Information System, Technology and Engineering, 2026)
Online customer support agents need to use internet-based systems because their work requires digital technology which raises their risk of cyber-loafing. The study investigates how technology accessibility affects online customer service workers' cyber-loafing behavior through its interaction with job stress and job boredom. The research used an explanatory design with its quantitative method to investigate the topic. The researchers gathered data through a survey which selected 170 participants using purposive sampling. The researchers conducted multiple linear regression analysis after they had completed data verification and reliability assessment and classical assumption testing. The study results showed that job stress and job boredom together with technology accessibility created a relationship which had a strong impact on cyber-loafing behavior. People in digital workplaces access non-work internet content according to this study because their mental states and workplace conditions determine their online habits. The research establishes a theoretical framework which develops our understanding of employee behavior in digital workplace settings. The study results provide organizations with practical recommendations on how to maintain employee productivity through effective management of their workload and work design and technology implementation.